Nurturing legal education awareness among school students: the way forward of building a just society / Nurul Mazrah Manshor, Dr. Rohayati Hussin and Nur Irinah Mohamad Sirat - Manshor, Nurul Mazrah; Hussin, Rohayati; Mohd Sirat, Nur Irinah (Universiti Teknologi MARA, Kedah, 2024)
Legal education awareness among school students plays a pivotal role in nurturing a society where citizens are cognizant of their rights and responsibilities. This writing explores the importance of integrating legal education into the school curriculum and elucidates its potential benefits in creating informed, responsible, and socially conscious individuals.